Impact of dual residual risk of cholesterol and inflammation on adult male sex hormones: a cross-sectional study from NHANES - Zhou, Yang; Wang, Guofeng; Liu, Li; Yu, Jie; Ju, Shiying (Frontiers in Endocrinology, 2025)
PurposeSex hormones are closely linked to inflammation and lipid metabolism. This study explores the correlation of residual cholesterol risk and residual inflammation risk with sex hormones.Materials and methodsLogistic regression and dose-response curve analyses were conducted to examine the associations of total testosterone (TT), Sex Hormone Binding Protein (SHBG), Estradiol (E2), and Free testosterone (FT) with low density lipoprotein cholesterol (LDL-C) and high sensitive c-reactive protein (hs-CRP). Testosterone deficiency, defined as TT below 300 ng/dL, was analyzed across various subgroups based on LDL-C and hs-CRP levels. Grouped by LDL-C and hs-CRP: normal, LDL-C < 2.6 mmol/L, hs-CRP < 3mg/L, residual cholesterol risk only (RCR): LDL-C ≥ 2.6 mmol/L, hs-CRP < 3mg/L, residual inflammation risk only (RIR): LDL-C < 2.6 mmol/L. hs-CRP ≥ 3mg/L, both risk (BR): LDL-C ≥ 2.6 mmol/L, hs-CRP ≥ 3mg/L.ResultsThe results indicated a negative association between hs-CRP and TT (β = -1.98, 95% CI [-3.54, -0.42], p = 0.013), as well as FT (β = -0.04, 95% CI [-0.07, -0.02], p = 0.0002). Similar trends were observed for the relationship between hs-CRP and SHBG (β = -3.61, 95% CI [-5.33, -1.90], p = 0.0003). In the presence of both risk factors (BR), TT decreased most significantly (β = -79.37, 95% CI [-112.74, -46.00], p < 0.0001), as did FT in the same subgroup (β = -1.00, 95% CI [-1.61, -0.40], p = 0.0012). Notably, hs-CRP exhibited a non-linear correlation with TT, SHBG, and FT, with distinct inflection points. Furthermore, in diabetic patients, hs-CRP was positively linked to E2 (β = 0.39, 95% CI [0.03, 0.74], p = 0.0328).ConclusionsLDL-C was independently correlated with SHBG, hs-CRP with TT and FT, and the BR population had a higher risk of testosterone deficiency. Special populations with diabetes and hypertension need to be concerned about residual cholesterol risk and inflammatory risk.